SYNTHESIS OF CHITOSAN FROM KIJING SHELLS (P. exilis) WITH THE ADDITION OF CHLOROACETIC ACID AND TRIPOLYPHOSPHATE CROSS-LINKER FOR Cu (II) METAL ADSORPTION - ihdal khairia; Hasri Hasri; Ahmad Fudhail Majid (Analit : Analytical and Environmental Chemistry, 2024)
The utilization of kijing clam shells as raw materials for chitosan production is one of the efforts to reduce kijing clam shell waste. This study is an experiment aimed at determining how to synthesize carboxymethyl chitosan (CM-Ch) and carboxymethyl chitosan-tripolyphosphate (CM-Ch-TPP), as well as the influence of pH and concentration of CM-Ch and CM-Ch-TPP on the adsorption of Cu(II) metal ions. The results showed that chitosan had a degree of deacetylation (DD) of 76%. Synthesized CM-Ch had characteristic functional groups at peaks 1610.56 cm-1 and 1425.4 cm-1. In the synthesized CM-Ch-TPP, there were functional groups at the peak of P=O stretch vibration and P-O stretch vibration at wave numbers 1213.23 cm-1 and 11,53.43 cm-1 in kijing. It is concluded that CM-Ch and CM-Ch-TPP have the ability to adsorb Cu(II) metal ions at pH 10 with concentrations ranging from 50 to 150 ppm.     The utilization of kijing clam shells as raw materials for chitosan production is one of the efforts to reduce kijing clam shell waste. This study is an experiment aimed at determining how to synthesize carboxymethyl chitosan (CM-Ch) and carboxymethyl chitosan-tripolyphosphate (CM-Ch-TPP), as well as the influence of pH and concentration of CM-Ch and CM-Ch-TPP on the adsorption of Cu(II) metal ions. The results showed that chitosan had a degree of deacetylation (DD) of 76%. Synthesized CM-Ch had characteristic functional groups at peaks 1610.56 cm-1 and 1425.4 cm-1. In the synthesized CM-Ch-TPP, there were functional groups at the peak of P=O stretch vibration and P-O stretch vibration at wave numbers 1213.23 cm-1 and 11,53.43 cm-1 in kijing. It is concluded that CM-Ch and CM-Ch-TPP have the ability to adsorb Cu(II) metal ions at pH 10 with concentrations ranging from 50 to 150 ppm.